Public and green spaces in the context of sustainable development - Vidal, Diogo Guedes (2019)
Public and green spaces are open areas and where the land is partly or completely covered with grass, trees, water sources, shrubs, or other types of vegetation. The typologies of public and green spaces are defined in accordance with a variety of criteria, such as size, facilities, or distance from the residential areas. In the scope of United Nations 2030 Agenda, public and green spaces play a vital role in the promotion of cities’ sustainability and citizens’ well-being, namely, in the connection between human and nature and also in the multiple benefits to human and environmental health. The access to public and green spaces with quality should be ensured by the local and central authorities in order to promote healthy and resilient cities, understood by the World Health Organization as a universal right.